Genome-Wide Identification and Characterization of Glycosyltransferase Family 47 in Cotton - Wu, Aimin; Hao, Pengbo; Wei, Hengling; Sun, Huiru; Cheng, Shuaishuai; Chen, Pengyun; Ma, Qiang; Gu, Lijiao; Zhang, Meng; Wang, Hantao; Yu, Shuxun (Frontiers in Genetics, 2019)
The glycosyltransferase (GT) 47 family has been verified to be involved in the biosynthesis of xylose, pectin and xyloglucan and plays an important role in maintaining the normal morphology of the plant cell wall. However, the roles of GT47s are less reported in cotton. In the present study, a total of 53, 53, 103 and 107 GT47 genes were detected by genome-wide identification in Gossypium arboreum, G. raimondii, G. hirsutum and G. barbadense, respectively. Phylogenetic analysis classified the GT47s into six major groups, A-F. The exon/intron structure and protein motifs indicated that each branch of the GT47 genes was highly conserved. Collinearity analysis showed that whole-genome duplication was the primary cause of upland cotton GT47 gene expansion and that segmental duplication played important roles in GT47 gene expansion within the At and Dt subgenomes. The Ka/Ks values indicated that the GT47 gene family was subjected to purifying selection during the long-term evolutionary process. Transcriptomic data and qRT-PCR showed that GhGT47 genes exhibited different expression patterns in each tissue and during fiber development. Our results suggested that some genes in the GhGT47 family might be associated with fiber development and abiotic stress response, which could promote further research involving functional analysis of the GT47 genes in cotton.